At the intersection of disaster risk and religion: interpretations and responses to the threat of Tsho Rolpa glacial lake. (2nd October 2017) - Sherry, Jennifer; Curtis, Allan
ABSTRACT: Over the last several decades, the scientific community has replaced the 'acts of god' explanations for disasters with a view that disasters are actually 'acts of nature, ' and more recently, 'acts of human behavior and decision making.' Despite the secular orientation of contemporary disaster research, religious beliefs still govern people's interpretations of natural events across many continents and cultures. Using a case study of a rural Sherpa community in Nepal, this paper responds to the challenge of linking religion and disaster risk in the context of a climate change-induced glacial lake outburst flood hazard. Data collection employed ethnographic techniques including participant observation and 53 interviews with community members. Results indicate that the case study community's religious belief system influences how they interpret and respond to the glacial lake hazard, although their beliefs co-exist with more scientific interpretations of risk. Rather than being immobilised by their belief system, we found that religious aspects like rituals and prayer can enhance social cohesion and contribute to capacities for coping with fear and uncertainty in this community. We assert that religion can yield valuable resources to glacial lake risk reduction strategies, which will benefit from incorporating social-cultural factors more profoundly.